Web app AdoptaPet: The application that facilitates the adoption and information of pets that need a home - Gutiérrez-Alvarado, Ibisay (2026)
This platform merges two key propositions: a web application for responsible pet adoption and an animal welfare management system called Pet’s History. The goal is to create a digital ecosystem that connects adopters, shelters and veterinarians, promoting responsible care and well-being of pets. This unified platform not only facilitates responsible adoption, but also ensures the continued well-being of pets through a comprehensive health and care management system. By connecting all the actors involved in the animal ecosystem, a community committed to the love and responsibility towards pets is promoted.